Lair of Dreams - Book 2 - Bray, Libba (New York, NY Little, Brown and Company, 2017)
After a supernatural showdown with a serial killer, Evie ONeill has outed herself as a Diviner and has become a media darling. In the meantime, a mysterious sleeping sickness has hit New York City, and the Diviners must band together to find the cause and the cure.
Keywords: Psychic ability -- Fiction; Nightmares -- Fiction; Dreams -- Fiction; Good and evil -- Fiction; New York (N.Y.) -- History -- 1898-1951; Fiction; Paranormal fiction; Young adult fiction; Fiction; History; Paranormal fiction; Young adult works